Characteristics Of A New Enhanced Recycled Polylactide For Sustainable 3D Printing Through Process Optimization - Zainal Aris, Muhamad Aminur 'Ilham (2020)
3D printing has been known as additive manufacturing which fabricate a three dimensional of the desired object, part, or assembly model very quickly in layers by using a 3D computer-aided design (CAD). The fast growth of inexpensive 3D printing machines has provided opportunities to users for making useful stuff even at their homes. Polylactide acid (PLA) filament is widely used as a material for 3D printing machines due to inexpensive cost yet has lower toxicity and higher in mechanical performance. However, the rapid growth of 3D printing desktop resulting in the polymer consumer to rise up. Furthermore, the finished products are always refused because of human error and technical error. The higher number of rejections 3D printed products causing the 3D printing waste to increase drastically. Therefore, this project is conducted to minimize the issue by developing a recycled PLA filament using a hand-build extruder machine. The objectives of this project are to optimize the parameters of extruding filament process through the Design of Experiment including analysing the mechanical and surface properties of recycled PLA filament. The optimization of critical process parameters for extruding recycled PLA filament was done using Minitab software. The extruding parameters evaluated are temperature, extruding speed, and extruder machine power. According to the analysis, the Taguchi method suggests an optimal value for every extruding process parameter. The PLA waste went through several processes which are washing process, cutting process and shredding process before proceeding to the extruding process. After recycled PLA filament has been made, analysis on diameter size for every 200 mm was done for the purpose of calculating percentage error. The percentage of error for the diameter of filament specifies 1.73mm diameter with 1.14% as the lowest error while the diameter of 1.60mm with 8.57% as the highest error. A five-set of dog-boned shape objects of recycled PLA filament and original PLA filament were fabricated using Fused Deposition Modelling (FDM). Mechanical properties for both specimens were evaluated through tensile testing using INSTRON 8872. The data showed that the recycled PLA filament and original PLA filament can absorb the same amount of maximum load and tensile stress which the percentage error of those properties obtained a similar value of 5.361 %. However, the value of Young’s Modulus for original PLA and recycled PLA specimens are 1863.55 MPa and 1781.80 MPa, respectively, which indicates that the original PLA filament is more flexible compared to recycled PLA filament. The experiment used Scanning Electron Microscope (SEM) for surface analysis of both filaments, the results illustrated that the surface of recycled PLA filament contained several air gaps while there are no defects on the surface of the original PLA filament. Overall, the utilization of recycling PLA filament in 3D printing machines can surely reduce waste pollution and also able to save a lot of money.